The Acoustic Dimension of Social Protest: Notes from an Ethnography of Sound - José Luis Martin; Santiago Fernández Trejo (Íconos)
In this article we analyse the role of sound in protest marches from an interactional communication perspective. We present an inter-disciplinary proposal for the development of a methodology suited for the ethnography of sound in the contemporary context. We also present the results of the application of this methodology in the context of the protests against the forced disappearance of the 43 students from Ayotzinapa, Guerrero in Mexico. The study questions the social modes of sound as the acoustic materialization of the communication processes within specific sound contexts.